Ameliorative Effects of 3-methyladenine and Chloroquine in 3-nitropropionic-induced Huntington’s Disease like Symptoms in Mice - Virdi, Jasleen Kaur; Kulshrestha, Ritu; Jaggi, Amteshwar Singh (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: To study the effect of 3-methyladenine and chloroquine phosphate on 3-nitropropionic acid induced Huntington’s disease-like symptoms in mice. Materials and Methods: 3-Nitropropionic acid was administered at the dose of 50 mg/kg, i.p. twice daily for 5 days for inducing Huntington’s disease like symptoms. 3-Methyladenine (15 and 30 mg/kg, i.p.) and chloroquine phosphate (25 and 50 mg/kg, i.p.) were administered 30 min before each 3-nitropropionic acid administration. The motor tests including, rota-rod, beam walking, lateral push test and open-field test, along with memory/cognitive test using object recognition test were performed on day 0, 3 and 6. The role of autophagy was assessed by measuring the levels of LC3II in the brain. Histopathological studies using H&E, nissl staining; and immunohistochemistry of neuron specific enolase and caspase-3 were also performed. Results: Administration of 3-nitropropionic acid caused a decline in the motor functions and cognitive abilities of the animals. The histopathological studies also indicated neuronal injury and neuronal loss in the striatal region. Treatment with 3-methyladenine and chloroquine ameliorated motor and cognitive parameters induced by 3-nitropropionic acid along with prevention of neuronal loss. Moreover, these pharmacological agents ameliorated altered levels of LC3II with 3-methyladenine and chloroquine administration indicated involvement of autophagy. Conclusion: Treatment with 3-methyladenine and chloroquine may improve the symptoms related with Huntington’s disease by preventing 3-nitropropionic acid-induced neurodegeneration possibly by inhibiting autophagy.
Keywords: Huntington’s disease; 3-nitropropionic acid; Autophagy; Chloroquine phosphate; 3-methyladenine